Pupuh Sinom as a Culture-Based Medium for Strengthening Hindu Spirituality among Balinese Youth - Luh Restia Dewi; I Made Suweta; I Nyoman Miarta Putra (LifeSciFi, 2026)
Globalization and digital technology challenge traditional arts, positioning pupuh sinom as a culture-based medium for Hindu spiritual education and preservation. This study aims to examine the use of pupuh sinom as a medium for fostering Hindu spirituality among the Sekaa Truna Truni in Tukadmungga Village, identify the spiritual values embedded in its verses, analyze its role in strengthening spiritual understanding, and explore the challenges encountered in its implementation. A qualitative descriptive approach was employed using observations, in-depth interviews, documentation, and literature review. The data were analyzed through an interactive qualitative analysis model involving data reduction, data display, and conclusion drawing. The findings indicate that pupuh sinom effectively promotes Hindu spirituality by internalizing the values of sraddha, bhakti, tri kaya parisudha, tat twam asi, and dharma, while simultaneously strengthening character development and preserving Balinese cultural heritage. However, its implementation is constrained by declining youth interest in traditional arts, language barriers, and limited instructional resources. This study concludes that pupuh sinom remains a relevant and sustainable medium for culture-based Hindu spiritual education and provides practical insights for strengthening youth character and preserving local cultural heritage.